PENGEMBANGAN INSTRUMEN EVALUASI PEMBELAJARAN PAI DENGAN MENGGUNAKAN MODEL TAKSONOMI BLOOM - Mubarak Tegar Jaya; Mohamad Rafin, Muhammad Mirza Nurrohman, Abdullah Ahmad Ghofur (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Learning evaluation plays an important role in the educational process, including in Islamic Religious Education (PAI) subjects. Evaluation is used to measure the achievement of student competencies and the effectiveness of learning. However, the success of the evaluation is greatly influenced by the quality of the instruments used. This article discusses the development of PAI learning evaluation instruments based on Bloom's Taxonomy, which includes cognitive, affective, and psychomotor domains. This taxonomy provides a framework for designing comprehensive evaluation instruments, which not only measure knowledge, but also attitudes and skills of students in a religious context. The application of Bloom's Taxonomy in PAI evaluation is expected to support the achievement of more holistic learning objectives, including academic outcomes as well as the formation of character and spiritual values. This article also provides practical guidance for educators in designing effective learning evaluations, in accordance with the demands of a more flexible and character-based curriculum.